Consequential resolution of conflicts for aircraft together due for deviation coursework angle - Закора, С.А. (Proceedings of National Aviation University, 2006)
The sequential conflict resolution method for multi-aircraft environment is proposed. The peculiarities of maneuvering surface modeling for multi-aircraft conflict resolution using basic turn models is considered.